Isolation of Mesenchymal Stromal Cells From Peripheral Blood of ST Elevation Myocardial Infarction Patients. Issue 7 (28th February 2017) - Pieper, Ina Laura; Smith, Rachel; Bishop, Joanna C.; Aldalati, Omar; Chase, Alex J.; Morgan, Gareth; Thornton, Catherine A.
Abstract: Bone marrow mesenchymal stromal cells (MSCs) have shown therapeutic potential in the treatment of myocardial infarction patients. However, bone marrow requires invasive harvesting techniques. Therefore, the aim was to carry out a feasibility study of using autologous peripheral blood (PB) as a source for MSCs and platelet lysate (PL), a potential novel therapeutic intervention in acute ST elevation myocardial infarction (STEMI) patients. Autologous PL and MSCs were prepared from STEMI patient and healthy control blood. MSCs were analyzed by trilineage differentiation and flow cytometry. PB MSCs were isolated from 83% of patients ( n = 6) but not from controls. The use of PL was feasible in the first passage but not in subsequent ones due to volume. To conclude, PB is a promising alternative to bone marrow. It negates the need for invasive harvesting techniques, and reduces hemorrhagic risk in this patient population routinely managed with anticoagulant and antiplatelet agents.